Synthesis of tio2/ zno co-doped with nitrogen and sulfur and its photocatalytic activity in removal of reactive black 5 / Nur Najwa Yunus - Yunus, Nur Najwa (2020)
Photocatalytic degradation is identified as one of the effective, eco-friendly and fast process, but high energy-intensive as it utilizes UV irradiation. This drawback is possibly overcome by utilization of visible light, another readily abundant and free resource. In this study, TiO2/ ZnO co-doped N, S was used since the presence of N and S gives the finer grain size, red absorption and high photocatalytic activity. The precursor of TiO2, ZnO were titanium (IV) isopropoxide (TTIP) and zinc acetate respectively. Meanwhile the sources of nitrogen and sulfur were ammonium nitrate and thiourea. TiO2/ ZnO co-doped N, S photocatalyst was prepared via sol-gel method. The photocatalyst was analysed by using XRD, BET, FESEM and UV-vis DRS. The synthesized photocatalyst able to produce good crystallinity, small crystallite size (15.6 nm) and low surface area. The surface morphology of the photocatalyst is dense and has a little agglomeration. However, the energy band gap was reduced to 2.89 eV. The photocatalyst was calcined at temperature range between 400 to 800 °C. Their crystallite sizes and crystallinity increased proportionally with the calcination temperature. Then, the photocatalyst was subjected into photodegradation study by using RB5 as the model pollutant. Different factors which may affect the rate of photodegradation were tested which are the effect of calcination temperature, catalyst loading, pH and initial concentration of RB5. From the findings, the optimum parameters are calcination temperature=600 °C, catalyst loading=3 g/L, pH=6 and initial concentration=5 mg/L. The optimum parameters were used again in optimization study and the apparent degradation rate of constant was 3.917×10-3 min-1.